2018
DOI: 10.7554/elife.37344
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility dynamics across C. elegans development and ageing

Abstract: An essential step for understanding the transcriptional circuits that control development and physiology is the global identification and characterization of regulatory elements. Here, we present the first map of regulatory elements across the development and ageing of an animal, identifying 42,245 elements accessible in at least one Caenorhabditis elegans stage. Based on nuclear transcription profiles, we define 15,714 protein-coding promoters and 19,231 putative enhancers, and find that both types of element… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 89 publications
(160 reference statements)
3
129
0
Order By: Relevance
“…We found that an increase in chromatin accessibility at regulatory elements primes genes for future activity. Although changes in chromatin accessibility have been correlated with transcription levels before [10,70,71], it was not clear whether chromatin accessibility at regulatory regions primes genes for activation. Here, we show directly that the increase in accessibility during the earliest stages of zygotic genome activation has a strong predictive value for future transcription.…”
Section: Pou5f3 Sox19b and Nanog Prime Genes For Activationmentioning
confidence: 99%
“…We found that an increase in chromatin accessibility at regulatory elements primes genes for future activity. Although changes in chromatin accessibility have been correlated with transcription levels before [10,70,71], it was not clear whether chromatin accessibility at regulatory regions primes genes for activation. Here, we show directly that the increase in accessibility during the earliest stages of zygotic genome activation has a strong predictive value for future transcription.…”
Section: Pou5f3 Sox19b and Nanog Prime Genes For Activationmentioning
confidence: 99%
“…C. elegans clearly establishes new promoters and new sites of active histone modification as development proceeds (Daugherty et al 2017;Janes et al 2018), which we detect as the late appearance of H3K27ac and nascent RNA at annotated DAC regions (Figure 2a, Supplemental Table 2). The activation of these in the late embryo is coincident with the expected transcription of lineage-specific mRNAs (Levin et al 2016) associated with terminal, differentiated cell fates (Boeck et al 2016;Packer et al 2019a).…”
Section: Chromatin Maps Hyperaccessible Regions and Enhancersmentioning
confidence: 81%
“…promoter-associated RNAs, eRNAs) (Chen et al 2013;Daugherty et al 2017;Ho et al 2017). But, given the questionable distinction between enhancers and promoters (Henriques et al 2018), the understanding of enhancer function in C. elegans is incomplete (Barriere and Ruvinsky 2014;Janes et al 2018). We suspect that gene regulation in C. elegans is generally not reliant on chromatin insulation or classical gene enhancers that can function irrespective of orientation and position that are used in other eukaryotes.…”
Section: Gene Control Without Insulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pervasive antagonistic coevolution is a potentially critical mechanism that drives the animal kingdom (~7.77 million species (Mora et al, 2011;Strain, 2011)) to engender far more diverse species compared to the plant kingdom (~298K species (Mora et al, 2011)) under continual natural selection. Growing evidence shows that both tumors (Francis et al, 2019;Jin et al, 2019;Perera et al, 2016) and ageing (Janes et al, 2018;O'Callaghan and Vassilopoulos, 2017;Stegeman and Weake, 2017) are correlated with the interactions of promoters and TFs. The promoter-TF coevolutionary trajectories in the animal kingdom will shed further light on the mechanisms underlying tumor initiation and progression as well as human ageing, which are yet to be fully understood.…”
Section: Discussionmentioning
confidence: 99%